2003
DOI: 10.4049/jimmunol.170.3.1202
|View full text |Cite
|
Sign up to set email alerts
|

Broadening of Epitope Recognition During Immune Rejection of ErbB-2-Positive Tumor Prevents Growth of ErbB-2-Negative Tumor

Abstract: Tumor heterogeneity is a limiting factor in Ag-specific vaccination. Ag-negative variants may arise after tumor cells bearing the immunizing Ags are destroyed. In situ priming to tumor-associated epitopes distinct from and not cross-reactive with the immunizing Ags may be crucial to the ultimate success of cancer vaccination. Immunization of BALB/c mice with DNA encoding wild-type human ErbB-2 (Her-2/neu, E2) or cytoplasmic ErbB-2 (cytE2), activated primarily CD4 or CD8 T cells, respectively, and both vaccines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…21,22 We have concentrated on developing this targeted rrVSV to improve the already excellent safety profile of wild-type VSV. rrVSV therapy was able to eliminate 1-day-old microscopic peritoneal tumor implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 We have concentrated on developing this targeted rrVSV to improve the already excellent safety profile of wild-type VSV. rrVSV therapy was able to eliminate 1-day-old microscopic peritoneal tumor implants.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that this rrVSV selectively infected, replicated and killed cells expressing erbb2. 21,22 rrVSV therapy was able to eliminate 1-day-old microscopic peritoneal tumor implants of D2F2/E2 cells, a BALB/c mouse mammary tumor cell line which was stably transfected to express Her2/neu. 23 We now attempted to treat macroscopic nodules of compact tumor because the structural and immunological challenges preventing successful therapy are fundamentally greater than those posed by small loose collections of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…These results were somewhat different from earlier reports showing that the protection mediated by HER2/neu DNA vaccine in conjunction with GM-CSFencoded plasmid is predominantly CD4 þ T-cell dependent. 18,19 Surprisingly, the bicistronic expression plasmid appeared to be more potent as the genetic adjuvant than combination of two monocistronic plasmids in activating DC and enhancing cytolytic activities of natural killer (NK) and T cells in the murine mouse bladder tumor-2 (MBT-2) tumor model. Taken together, our results suggest that coexpression of Flt3L and GM-CSF represents a promising strategy to modulate the class of antitumor immune responses and enhance the efficacy of DNA vaccines against tumor-associated antigens.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Furthermore, CD4 þ T cells are the primary antitumor effectors induced by HER2/neu and GM-CSF DNA immunization. 18,19 In this study, we exploited HER2/neu DNA vaccine to study the adjuvant effect of murine Flt3L and GM-CSF in different forms of plasmid construction. We show that coexpression of Flt3L and GM-CSF as genetic adjuvants induced a CD8 þ T-cell-mediated antitumor immune response.…”
Section: Introductionmentioning
confidence: 99%
“…These long-term survivors have also shown 50% protection after subsequent challenge with the parental cell line not expressing HER2/neu (80). In this case, challenge with the HER2/neu expressing tumors may have resulted in priming of the immune system and broadening of epitope recognition mediated by CD8 + T cells against D2F2 cells not expressing human HER2/neu.…”
Section: Discussionmentioning
confidence: 96%